“BIAR KALAH NASI MAR JANGAN KALAH AKSI” STUDI KASUS PASTORAL TERHADAP GAYA HIDUP HEDONIS PADA MASYARAKAT KOTA MANADO - Hesky C Opit; Ryanto Fadly Sumendap (Institut Agama Kristen Negeri Manado, 2021)
The purpose of this paper is to explain about hedonism which is very influential in the cultural life of the Manadonese, this has become a habit or has been ingrained in the culture or lifestyle of the Manadonese, where the Manadonese like to party, in appearance must always be the best, do not want to look difficult, whereas in Christian teachings or values, things like that are not taught by God. The research location is taken in the Manado area and focuses on the habits or lifestyle of the Manadonese who behave hodonistically. The theory or approach taken is a gestalt pastoral approach and client center. The research method used is a pastoral case study methodology. Every human being does need something to satisfy himself, but if it will plunge them into a trap, then it is better not to overdo it, as much as possible so that you will not experience difficulties, and do not make an excessive lifestyle in everything as a benchmark for one's success, because success and Happiness is obtained when the person is able to live in peace and tranquility and feel sufficient in all his needs.